2020
DOI: 10.3390/plants9121790
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Salicylic Acid Modulates the Response to Combined Salinity-Temperature Stress in Pepper Plants (Capsicum annuum L. var. Tamarin)

Abstract: Growers in the cultivated areas where the climate change threatens the agricultural productivity and livelihoods are aware that the current constraints for good quality water are being worsened by heatwaves. We studied the combination of salinity (60 mM NaCl) and heat shock stress (43 °C) in pepper plants (Capsicum annuum L. var. Tamarin) since this can affect physiological and biochemical processes distinctly when compared to separate effects. Moreover, the exogenous application of 0.5 mM salicylic acid (SA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Applying Salicylic acid (SA) to the leaves has induced plant stress tolerance. Several studies have found that Salicylic acid (SA) has beneficial effects on plants in terms of resistance to salinity, drought, and high temperatures [105,180,181]. The previous results suggested that Salicylic acid (SA) helps plants adapt to abiotic stresses [182].…”
Section: Salicylic Acidmentioning
confidence: 99%
“…Applying Salicylic acid (SA) to the leaves has induced plant stress tolerance. Several studies have found that Salicylic acid (SA) has beneficial effects on plants in terms of resistance to salinity, drought, and high temperatures [105,180,181]. The previous results suggested that Salicylic acid (SA) helps plants adapt to abiotic stresses [182].…”
Section: Salicylic Acidmentioning
confidence: 99%
“…It might be ascribed to SA induced intensification Cl − ions in plants on account of increase in oxidative damage during high salt concentration. Accumulation of toxic anion (Cl −) in the leaves may possibly have compromised the photosynthetic machinery, which negatively alters growth 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Capsicum is very sensitive to low temperatures, and low-temperature stress can seriously affect its growth and development, limiting its yield and quality [12]. Many exogenous substances, such as brassinolide (Br), salicylic acid (SA), and 5-aminolevulinic acid (ALA), can alleviate the stress caused by low temperatures in capsicum [22][23][24]. The effect of H 2 S on low-temperature stress in pepper mostly remains at the physiological level, and data on the signaling pathway in response to low-temperature stress remain limited.…”
Section: Introductionmentioning
confidence: 99%